ECONOMIC EFFICIENCY OF TAX REFORMS IN UZBEKISTAN - Gulayim Bakhadyrovna Saparova; Shokhrukh Murtazaev (Innovation Science and Technology, 2025)
This article analyzes the economic efciency of the tax reforms implemented in Uzbekistan during 2017–2023. It examines key changes in the tax system, including the reduction of the tax burden, the introduction of digital tools, and the simplifcation of procedures for businesses. Based on statistical data, the study evaluates the impact of the reforms on business activity, the structure of state budget revenues, and the level of transparency in tax administration. The fndings highlight a positive but gradual eﬀect of the transformations and outline directions for further improvement of tax policy.